The Dynamics of Inflation in Latin America: Comment - Sheehey, Edmund J. (American Economic Review, 1976)
In a recent issue of this Review, Robert Vogel extended to sixteen Latin American countries a technique used by Arnold Harberger to examine the chief causes of Chilean inflation. On the basis of pooled regressions for the sixteen countries, he concluded that with little heterogeneity, the different rates of inflation cannot be put to structural differences but must be attributed to varying rates of expansion of the money supply. Only monetary variables are employed and the link between inflation and the rate of money suppl growth rests essentially on R2 so high as to leave little of the variation in the rate of price increase for other variables to explain. This note contends that in coming to such broad conclusions on the basis of only monetary variables, Vogel has committed an error that the Harberger model was designed to avoid. Some regressions based on Argentine data are presented by way of illustration. As a partial justification for using only monetary variables, Vogel states the Harberger model is essentially monetarist. In his original study, however, Harberger focused specifically on the problem of multicollinearity between changes in the money supply and the wage rate. He suspected that the long history of Chilean inflation consisted of instances when increases in the quantity of money had brought rising prices in the absence of wage increases, other instances when wages had pushed up prices without being by expansion of the money supply, and still others when inflation had been accompanied by wages and prices rising together. Regression analysis cannot sort out these instances, he asserted, . . . but it can g,ive some indications of their relative importance, and can surely distinguish between the extreme positions that deny the explanatory power of either wage changes or monetary changes, once the other is taken into account (p. 228). Thus Harberger contended that if either nmonetary changes or wage changes are excluded, the regression analysis might not be able to distinguish between these extreme positions. A formulation such as Vogel's, using money supply changes and lagged values of the rate of inflation, can capture the variation in prices resulting from: 1) current and past instances in which money supply changes alone have driven up prices; 2) current and past instances in which monetary and structural variables have risen in step; and 3) past instances in which structural variables alone have been at work. The only instances that it clearly will not capture are those in which current structural variables have operated without accompanying money supply changes. Vogel's high k2 indicate that these instances have been few relative to all others. However, because Vogel's model will attribute to monetary factors the variation in prices due to both current structural causes which have been financed by increases in the money supply and past causes which have affected the lagged price variable, these R2 cannot say anything about the relative importance of structural and monetary factors. The Harberger model is designed to identify the relative inflationary impact of structural and monetary factors when each has operated alone. If it is true that in the majority of instances both have operated together and that in an important number of instances, each has forced up prices on its own, then either a totally monetary model, such as Vogel's, or a totally structural one will leave only a small portion of the variation in prices unexplained. Their relative importance as independent inflationary forces will only show up in an equation which uses both sets of factors. * Economic affairs officer, General Agreement on Tariffs and Trade. I assume sole responsibility for the views expressed here.